2012
DOI: 10.4321/s1139-76322012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Atención a los recién nacidos en 2009 y a sus madres en un centro de salud urbano de Zaragoza: Oportunidades de mejora

Abstract: Atención a los recién nacidos en 2009 y a sus madres en un centro de salud urbano de Zaragoza. Oportunidades de mejora Introduction: in recent years has significantly changed the composition of the population and the origin of users of Torrero La Paz Health Primary Care Center of Zaragoza This work aims to analyze the social data and attention of the RN and their mothers corresponding to area of health of Torrero La Paz and throughout the year 2009. Authors are especially interested on rates of prevalence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…15 As for the factors that contribute to BF continuation, our study found a significant association with birth weights of more than 3 kg and gestational ages above 37 weeks, findings that have been reported in several other studies. 9,11,16,17 Consequently, BF rates are lower in preterm and lowbirthweight newborns, the populations that research shows derive the most benefit from breastfeeding. The separation of these newborns from their mothers should be avoided, as should be the initiation of artificial feeding, which could be replaced by the extraction and storage of breast milk, and strategies like the "kangaroo care" approach should be implemented.…”
mentioning
confidence: 99%
“…15 As for the factors that contribute to BF continuation, our study found a significant association with birth weights of more than 3 kg and gestational ages above 37 weeks, findings that have been reported in several other studies. 9,11,16,17 Consequently, BF rates are lower in preterm and lowbirthweight newborns, the populations that research shows derive the most benefit from breastfeeding. The separation of these newborns from their mothers should be avoided, as should be the initiation of artificial feeding, which could be replaced by the extraction and storage of breast milk, and strategies like the "kangaroo care" approach should be implemented.…”
mentioning
confidence: 99%